Complete Genome Sequence and Characterization of a Protein-Glutaminase Producing Strain, Chryseobacterium proteolyticum QSH1265 - Qu, Ruidan; Zhu, Xiaoyu; Tian, Min; Liu, Yingjie; Yan, Wenjuan; Ye, Jian; Gao, Hongliang; Huang, Jing (Frontiers in Microbiology, 2018)
Recently, an enzyme named protein-glutaminase (PG) has been identified as a new type of enzyme with significant potential for deamidation of food proteins. The enzyme is shown to be expressed as a pre-pro-protein with a putative signal peptide of 21 amino acids, a pro-sequence of 114 amino acids and a mature PG of 185 amino acids. The microbial enzyme PG specifically catalyzes deamidation of proteins without protein hydrolysis pretreatment and only reacts with glutamine residues in the side-chains of proteins or long peptides. All these attributes suggest that it has a great potential for food industrial applications. However, until recently, there have been relatively few studies of the PG-producing strains. A strain named Chryseobacterium proteolyticum QSH1265 which can produce PG was isolated from a soil sample collected in Songjiang, Shanghai, China. Its enzyme activity was about 0.34±0.01 U/mL when using carboxybenzoxy-Gln-Gly as a substrate. The strain can produce acid from D-glucose, maltose, L-arabinose sucrose, glycerol and mannitol but not fructose, and it is also positive for indole production and urease. Here we describe the complete genome sequence of this strain via PacBio RSII sequencing. The Chryseobacterium proteolyticum QSH1265 genome consists of a circular chromosome with total length of 4,849,803bp without any plasmids. All of 4563 genes were predicted including 4459 genes for protein-coding and 104 RNA-relative genes with an average G+C content of 36.16%. The KEGG and COG annotation provide information for the specific function of proteins encoded in the genome, such as proteases, chromoproteins, stress proteins, antiporters, etc. A highly conserved hypothetical protein shares a promoter with the gene encoding the protein-glutaminase enzyme. The genome sequence and preliminary annotation provide valuable genetic information for further study of Chryseobacterium proteolyticum.